A case of Cryptococcus laurentii meningitis in an immunocompromised patient: case report - Bhalavi, Sangeeta; Shendre, Pooja; Lyngdoh, Da I Nesha Banylla; Channe, Nirmal; Shrikhande, Sunanda (International Journal of Research in Medical Sciences, 2026)
Cryptococcosis is an important opportunistic fungal infection among immunocompromised, AIDS patients and those under immunosuppressive therapy. While C. neoformans and C. gattii are the most common pathogens attributed to cryptococcosis, C. laurentii infections are also on the rise. Here, we report a case of meningitis caused by C. laurentii in an HIV infected, male patient with a low CD4+ T cell count. C. laurentii, though rare, has been reported as an etiological agent of cutaneous, pulmonary, disseminated and ocular infections in AIDS as well as HIV negative individuals. Species differentiation is necessary as C. laurentii has been reported to have higher resistance to azoles and flucytosine. Infections caused by Cryptococcus non-neoformans infection are rare and require extensive investigation to be substantiated. Increasing reports of infection caused by other cryptococcal species, can be attributed to the growing number of immunocompromised and debilitated patients with predisposing factors, improvements in their detection and identification, and enhanced awareness of such non-typical infections.